2017
DOI: 10.1186/s12885-017-3309-2
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic non-muscle invasive bladder cancer with meningeal carcinomatosis: case report of an unexpected response

Abstract: BackgroundNon-muscle invasive bladder cancer (NMIBC) is usually treated with local therapy including transurethral resection of the bladder tumor and intravesical therapy depending on the stage of the tumor. NMIBC is a rarely a metastatic diseases with lymph node invasion in less of 10%. In the other hand meningeal carcinomatosis is a rare location for metastases with extremely poor outcomes. We described a case report of a patient presenting a metastatic disease to bones and meninges, several years after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Even in non-muscle-invasive bladder cancer, a case of MC with multiple bone metastases following transurethral resection with intravesical Bacillus Calmette-Guerin instillation was reported (case no. 32, Table I) (27). MC had already developed at initial diagnosis of bladder cancer in 4 cases (16.7%).…”
Section: Discussionmentioning
confidence: 95%
“…Even in non-muscle-invasive bladder cancer, a case of MC with multiple bone metastases following transurethral resection with intravesical Bacillus Calmette-Guerin instillation was reported (case no. 32, Table I) (27). MC had already developed at initial diagnosis of bladder cancer in 4 cases (16.7%).…”
Section: Discussionmentioning
confidence: 95%
“…At least 2 cases of distant bone metastasis in non–muscle invasive disease have been reported in the literature. 4 , 18 In one case, a patient with stage T1HG showed no evidence of lymphovascular invasion or muscle invasive disease at the initial TURBT or the subsequent restaging TURBT. 18 As the patient’s primary tumor location made complete resection difficult, a partial cystectomy was performed, and lymphadenectomy at that time showed no evidence of regional metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The most common reported sites of metastasis for UC are liver (47%), lung (45%), or bone (32%). 4 While bone may be a frequent site of metastasis, the bones of the skull are infrequently involved. We report here the 13th known case of UC metastatic to the jaw.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of NB, cisplatin, as a frontline chemotherapy agent, which can deliver damage to DNA, often fails to exert tumor-suppressing effects, as a result of a decreased sensitivity of the tumor cells [42]. Studies have shown that GATA3 is associated with cisplatin chemoresistance in high-grade serous ovarian carcinoma [17] and nonmuscle invasive urothelial carcinoma [43]. In agreement with the role of GATA3 to support cisplatin chemoresistance in high-grade serous ovarian carcinoma, our study confirmed that GATA3 expression was negatively correlated with the sensitivity of CHP-212 cells and SK-N-AS cells to cisplatin, suggesting that GATA3 confers cisplatin chemoresistance on NB cells.…”
Section: Discussionmentioning
confidence: 99%